2011
DOI: 10.1080/00273171.2011.569408
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Paper and Online Tests Using a Within-Subjects Design and Propensity Score Matching Study

Abstract: This inquiry had 2 components: (1) the first was substantive and focused on the comparability of paper-based and computer-based test forms and (2) the second was a within-study comparison wherein a quasi-experimental method, propensity score matching, was compared with a credible benchmark method, a within-subjects design. The tests used in the comparison of online tests and paper-based tests were End-of-Course tests in Algebra and English, in a statewide high school testing program. Students were tested in Gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(32 citation statements)
references
References 8 publications
2
30
0
Order By: Relevance
“…Consistent with what can be expected from the covariates balance results, the two propensity score matching approaches (i.e., the Lottridge et al, 2011, and the OPM-OBT approach) are most alike in classifying students based on the raw scores associated with the proficiency cuts. However, we also observed that the scale scores at the proficiency cuts are most alike for the modified MSCA and the Lottridge et al (2011) approach. We thus inferred that a different nonlinear relationship was established between raw scores and scale scores for the three matched PPT data sets.…”
Section: Resultssupporting
confidence: 68%
See 3 more Smart Citations
“…Consistent with what can be expected from the covariates balance results, the two propensity score matching approaches (i.e., the Lottridge et al, 2011, and the OPM-OBT approach) are most alike in classifying students based on the raw scores associated with the proficiency cuts. However, we also observed that the scale scores at the proficiency cuts are most alike for the modified MSCA and the Lottridge et al (2011) approach. We thus inferred that a different nonlinear relationship was established between raw scores and scale scores for the three matched PPT data sets.…”
Section: Resultssupporting
confidence: 68%
“…Consequently, some statistical methods have been proposed to obtain comparable PPT and CBT samples without the need for students to take a test in both modes. Two approaches are matched samples comparability analyses (MSCA; Way, Davis, & Fitzpatrick, 2006;Way et al, 2008) and propensity score matching (e.g., Lottridge et al, 2011). Propensity score matching and the MSCA method are similar in attempting to create statistically matched samples (Way et al, 2008), though the latter seems to match only on previous achievement scores (Way et al, 2006(Way et al, , 2008.…”
Section: Comparability Study Designsmentioning
confidence: 99%
See 2 more Smart Citations
“…In order to compare End-of-Course assessments in Algebra I and English I, Lottridge, Nicewander, and Mitzel (2011) had participants complete PBT and CBT versions of a multiple-choice assessment created by the state. Computer skills, reading scores, math scores, areas of the state, free and reduced lunch status, special education/gifted status, and ethnicity were all included in the analysis.…”
Section: Participant Factorsmentioning
confidence: 99%